Wood's lamp examination of hair and nails related to COVID-19 treatment - Demir, Betul; Cicek, Demet; Turkoglu, Sedatcan; Bozdemir, Neslihan Yuksel; Sarikurt, Furkan; Banoglu, Erden (Wiley, 2021)
[Abstract Not Available]
Keywords: Drugs